Genetic diversity assessment of winged bean [Psophocarpus tetragonolobus (L.) DC.] accessions using agronomic and seed morphometric traits - Bhadmus, A.; Abberton, M.; Idehen, E.O.; Ekanem, U.O.; Paliwal, R.; Oyatomi, O. (MDPI, 2023)
Winged bean [Psophocarpus tetragonolobus (L.) DC.] is an underutilized legume with the potential to contribute to nutrition and food security globally, particularly in sub-Saharan Africa (SSA). However, more attention needs to be paid to exploiting its full potential due to a lack of adequate knowledge of the existing genetic diversity in the available winged bean germplasm. To bridge this gap, thirty accessions of winged beans sourced from the Gene Bank of the International Institute of Tropical Agriculture (IITA), Ibadan, were evaluated for seed morphometric and selected agro-morphological traits at three agro-ecological zones in Nigeria. The data obtained were subjected to analysis of variance (ANOVA), principal component (PC) analysis, cluster analysis, and correlation analysis. Significant differences (p < 0.05) were observed among the accessions for all measured traits. The first two PCs accounted for 88.2% of the variation observed among the accessions for all measured traits. Accessions were grouped into three clusters based on the agro-morphological traits and three clusters under the multi-spectral imaging (MSI) system. TPt-31 had the highest seed yield per plant, pod weight per plant, and early maturity, while TPt-7 had an extended flowering and maturity period, the highest number of pods per peduncle and pods per plant, as well as the lowest seed yield. These accessions could be a good resource for future winged bean improvement programs. The result also confirmed that the MSI system is an invaluable tool for discriminating among accessions of the same crop species. The findings of this study provide insight into the genetic diversity of winged bean germplasm, which could contribute to improving its yield and quality in SSA and globally.